The Influence of Market Reaction on Capital Structure Moderated by Economic Package Policies - Nurhayati (Journal of Economicate Studies, 2021)
The economic crisis in Indonesia was influenced by the 2015 devaluation of China . This prompted the Government to issue an economic policy to stabilize the economy in Indonesia. This study aims to prove empirically how market reactions affect the capital structure before economic policy moderation. and the effect of market reactions on capital structure after being moderated by economic policies on property companies listed on the Indonesia Stock Exchange from 2015 to 2018. The dependent variable in this study is capital structure, the independent variable is market reaction and the moderating variable is economic policy. This study uses descriptive verification methods to determine the effect of market reactions on capital structure, and event study methods to determine how economic policies affect market reactions that will affect capital structure. by measuring the difference in abnormal returns and trading volume activity, which is a proxy for market reactions before and after the issuance of economic policies. Economic policy related to this research is economic policy related to property companies. The SPSS application was used in this study, and used moderated regression analysis. The results showed an increase in the effect of market reactions on the capital structure after the issuance of economic policies relating to property companies and economic policy moderation occurred which increased market reactions that had an effect on the capital structure. Economic policy is the application of development policies that encourage people to invest, which is reflected in market reactions which then affect the capital structure. This article examines how the concept of market reaction affects the structure of capital before and after the announcement of economic policy.